The impact of governance on political stability in Jordan (2002–2022) - Ala Alkhawaldeh (Frontiers in Political Science)
This study examines the influence of governance on political stability in Jordan from 2002 to 2022. The objective is to assess the correlation between governance and political stability by investigating many facets of governance, including the rule of law, governmental efficacy, anti-corruption measures, and regulatory quality, to ascertain their influence on political stability in Jordan. A quantitative analytic technique employing time series and sophisticated statistical methods was utilized, including unit root tests (ADF and PP) to assess data stationarity, and the Johansen cointegration test to examine long-term correlations among variables. Ordinary least squares (OLS) regression analysis was utilized to assess the direct influence of governance characteristics on political stability. The study's shortcomings stem from its exclusive emphasis on time series data for Jordan over a specific timeframe, potentially impacting the generalizability of the findings to other situations. The findings indicated that the rule of law was the predominant factor influencing political stability, whereas legislative competence and government performance exerted a lesser influence. The findings indicated a substantial cointegration connection between governance and political stability, underscoring the significance of effective governance in fostering political stability in Jordan.